Current Strategies for Tumor Photodynamic Therapy Combined With Immunotherapy - Hua, Jianfeng; Wu, Pan; Gan, Lu; Zhang, Zhikun; He, Jian; Zhong, Liping; Zhao, Yongxiang; Huang, Yong (Frontiers in Oncology, 2021)
Photodynamic therapy (PDT) is a low invasive antitumor therapy with fewer side effects. On the other hand, immunotherapy also has significant clinical applications in the treatment of cancer. Both therapies, on their own, have some limitations and are incapable of meeting the demands of the current cancer treatment. The efficacy of PDT and immunotherapy against tumor metastasis and tumor recurrence may be improved by combination strategies. In this review, we discussed the possibility that PDT could be used to activate immune responses by inducing immunogenic cell death or generating cancer vaccines. Furthermore, we explored the latest advances in PDT antitumor therapy in combination with some immunotherapy such as immune adjuvants, inhibitors of immune suppression, and immune checkpoint blockade.